Digital Competence and Capability Frameworks in Higher Education: Importance of Life-long Learning, Self-Development and Well-being - Biggins, D.; Holley, D.; Zezulkova, M. (EAI Endorsed Transactions on e-Learning, 2017)
The paper compares the EU’s 2013 and 2016 digital competence (DigComp) framework with the UK education’s 2009 and 2015 digital capabilities (DigCap) framework. The similarities are in the increased focus on data within privacy/overall literacy and the inclusion of well-being. Among the differences, DigComp focuses on life-long learning whereas DigCap is more holistic. This is explained by diverse target audiences, as DigComp has to be relevant to various stakeholders across the EU, whilst DigCap serves the UK higher and further education sector. Although education is dominant within DigCap, both frameworks agree on the importance of digital skills, knowledge and attitudes to the fields of education, training and employment. The paper discusses a UK HE case study of a technology enhanced learning toolkit. It concludes by arguing for a human-centred approach to digital competence and capability frameworks, in which learning, self-development and well-being play a vital role.
Keywords: competence; capability; framework; TEL; toolkit; education; well-being